FAKTOR - FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - FRISKA FIRNANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
The firm increases its value through managing capital structure decision. Thus, management of capital structure and decisions are important matter regarding the relationship between value of the firm and capital cost . There are several theories about capital structure, which explain capital structure decision making by management, such as asymmetric information theory, agency theory, static trade off theory, and pecking order theory. Objectives of the research are to examine and analyze the impact of the firm size, profitability, business risk, time interest earned, and asset growth to capital structure of the manufacturing firm listed in Indonesia Stock Exchange. Samples are taken by using purposive or judgement sampling method. Research has been done on 213 observations. The result shows that profitability,time interest earned, and asset growth have significant impacts to capital structure.On the other hand, size and business risks do not have significant impact on firm capital structure. The next reasearch is suggested to be done by comparing sectors of the firm in a longer period of time to get a more comprehensive result.